Implementation of blockchain technology in digital financial management systems - Murtopo, Aang Alim; Anshori, Abu Hasan Al; Santoso, Nugroho Adi; Gunawan, Gunawan (Jurnal Mandiri IT, 2024)
This research aims to develop and test a digital financial management system model that is integrated with blockchain technology to address security, transparency, and efficiency issues in the traditional digital financial system. Blockchain technology is used to ensure the integrity and security of data by recording each transaction in the form of interlinked and immutable blocks. The methods used include experimental approaches, quantitative analysis, and model validation. The results of the study show that blockchain integration improves the transparency, security, and operational efficiency of digital financial management systems. Although the designed asset recording application still has weaknesses in UX and UI, such as the lack of drop-down features and manual data entry, blockchain technology has successfully strengthened data security with the use of unique record IDs (hashes) that cannot be changed and public transparency through Etherscan. This research makes a practical contribution to the application of blockchain technology in the financial industry and suggests further development to improve the user experience and add features that improve the efficiency and flexibility of the asset recording system. These findings support the potential of blockchain in advancing the integrity and performance of the digital financial system.